Contesting space and power: Rethinking Habermas’s public sphere on the Madurese paternalistic ideology - Syamsu Budiyanti; Hotman M. Siahaan; Kris Nugroho (Universitas Trunojoyo Madura, 2022)
The public sphere is not always what Jürgen Habermas imagines, which is inclusive, egalitarian and pressure-free. In the Madurese paternalistic constellation, the dominations of power over the contestation of public opinion and action become prominent in the relationship between participants/actors. A meeting between different interests causes this contestation. The struggle for influence is also shown by the dominance of ‘capital’ or resources. In Madura, Kiai are considered to have ‘charismatic’ symbolic capital related to the historical and cultural aspects of the Madurese ethnicity. This makes the figure of Kiai (along with Blater as a twin regime) become the center of consensus-making in a paternalistic public discussion. This phenomenological qualitative research becomes interesting when the world view of the local community is connected with Habermas’ perspective through the idea of European version of the bourgeois public sphere, which is considered not applicable to the local genius Madurese realm. The arena of public sphere in the Tanean Lanjhang pattern and the existence of ‘langgar’ (mosque) in the social community rejects the characterization of Habermas and brings a new definition of Madurese paternalistic public sphere, which is hegemony-mutualistic, as one of the richness of Indonesian cultural patterns.